Proceedings of the 26th Annual Virtual Congress of the International Liver Transplantation Society. Issue 9 (19th August 2022) - Kalisvaart, Marit; Chadha, Ryan; De Martin, Eleonora; Alconchel, Felipe; Goldaracena, Nicolas; Keskin, Onur; Liu, Jiang; Nasralla, David; Mazzola, Alessandra; Rammohan, Ashwin; Spiro, Michael; Tanaka, Tomohiro; et al.
Abstract : After a 1-y absence due to the coronavirus disease 2019 pandemic, the 26th Annual Congress of the International Liver Transplantation Society was held from May 15 to 18, 2021, in a virtual format. Clinicians and researchers from all over the world came together to share their knowledge on all the aspects of liver transplantation (LT). Apart from a focus on LT in times of coronavirus disease 2019, featured topics of this year's conference included infectious diseases in LT, living donation, machine perfusion, oncology, predictive scoring systems and updates in anesthesia/critical care, immunology, radiology, pathology, and pediatrics. This report presents highlights from invited lectures and a review of the select abstracts. The aim of this report, generated by the Vanguard Committee of International Liver Transplantation Society, is to provide a summary of the most recent developments in clinical practice and research in LT. Abstract :